2018
DOI: 10.1124/jpet.118.250936
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-Like Prostaglandin D Synthase but Not Hemopoietic Prostaglandin D Synthase Deletion Causes Hypertension and Accelerates Thrombogenesis in Mice

Abstract: Prostaglandin (PG) D2 is formed by two distinct PGD synthases (PGDS): lipocalin-type PGDS (L-PGDS), which acts as a PGD2-producing enzyme and as extracellular lipophilic transporter, and hematopoietic PGDS (H-PGDS), a σ glutathione-S-transferase. PGD2 plays an important role in the maintenance of vascular function; however, the relative contribution of L-PGDS– and H-PGDS–dependent formation of PGD2 in this setting is unknown. To gain insight into the function played by these distinct PGDS, we assessed systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…A recently published article showed that LPGDS knock-out mice but not hPGDS knock-out mice display a cardiovascular phenotype. In the vasculature, an autocrine LPGDS-derived PGD 2 effect seems crucial to protect from hypertension and thrombogenesis [4].…”
Section: Hematopoietic Pgds Expression In Leukocytes and Parenchymmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published article showed that LPGDS knock-out mice but not hPGDS knock-out mice display a cardiovascular phenotype. In the vasculature, an autocrine LPGDS-derived PGD 2 effect seems crucial to protect from hypertension and thrombogenesis [4].…”
Section: Hematopoietic Pgds Expression In Leukocytes and Parenchymmentioning
confidence: 99%
“…Notably, in contrast to COX inhibition, specific inhibition of unfavourable pro-inflammatory PGD 2 effects and its metabolites would keep physiological functions of beneficial mediators like PGE 2 and prostacyclin intact. In mice, about 90% of the systemic biosynthesis of PGD 2 is generated by the hematopoietic PGD synthase (hPGDS)-dependent pathway and only partially through lipocalin-type PGD synthase (LPGDS) [4]. Most prostaglandins are generated by competitive enzymatic interactions, however, it has been suggested that prostaglandins may also be generated from precursor eicosanoids by non-enzymatic conversion [5], which also needs to be taken into account in a therapeutic setting.…”
Section: Introductionmentioning
confidence: 99%
“…In the milk somatic cells, the heat challenge induced the expression of a gene which regulates vasodilation and involved in thermoregulation. The pharmacological activities of prostaglandin D2 receptor 2 (PTGDR2) include vasodilation and bronchoconstriction [35][36][37] . Other functional roles of PTGDR2 are in thermoregulation and fever response 38 .…”
Section: Discussionmentioning
confidence: 99%
“…BTP synthesis is induced in endothelial cells under shear stress. Through prostaglandin D2 synthesis, BTP exerts vasodilating effects [52]. However, the role of BTP in endothelial dysfunction associated with systemic inflammation or sepsis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%